Pola Pikir Mahasiswa Dalam Menyelesaikan Permasalahan Pada Mata Kuliah Persamaan Diferensial - Kartikasari, Merisa; , Rita Pramujiyanti Khotimah,S.Si, M.Sc (2015)
This research intended to describe the pattern of thinking of students in solving problems of differential equations in terms of cognitive styles and learning styles. This type of research is qualitative descriptive. The subjects were students of class VE FKIP UMS Math. The technique of collecting data through observation, in-depth interviews, documentation and questionnaires. The data validity use methodology triangulasm which integrate documentation, observation, and interview. The data analysis technique used is the model analysis Miles and Huberman. The results showed that mindset VE grade students FKIP UMS Mathematics Education in solving problems of differential equations in terms of FI and FD cognitive styles and learning styles Activists, Reflectors, Theorists, and Pragmatists generally obtain information by reading and focus by writing information in about. On planning issues, the students perform analogical reasoning from about lesson study to problem solving test and implement appropriate plans and perceptions of their initial interpretation. In step recheck the answer, the student does not check the answers in writing.